In Vitro Anticoagulant Properties of a Minimum Functional Fragment of Human Thrombomodulin and In Vivo Demonstration of its Benefit as an Anticoagulant in Extracorporeal Circulation Using a Monkey Model - Suzuki, Makoto; Mohri, Mitsunobu; Yamamoto, Syuji (Thrombosis and Haemostasis, 1998)
Recently, we demonstrated that the last three consecutive epidermal growth factor-like structures of human thrombomodulin form the minimum functional fragment for protein C activating activity. In this study, the recombinant minimum functional fragment of human thrombomodulin (E456) had similar activities for protein C activation and clotting time compared to the recombinant extracellular domains of human thrombomodulin (rhsTM) previously described. E456 had a shorter half-life (6-9 min) in animals, compared to rhsTM (5 h). To evaluate whether or not E456 is a suitable anticoagulant for extra-corporeal circulation, the effects of E456 were investigated in the extracorporeal circulation model in monkeys. The effect of E456 at a dose of 0.03 mg/kg plus 0.113 mg/kg/h on circuit pressure was as potent as that of low molecular weight heparin, Fragmin, at a dose of 30 IU/kg plus 15IU/kg/h. E456, however, also more effectively suppressed an increase of thrombin-antithrombin III complex than Fragmin. Also the APTT quickly returned to the pre-treatment level following E456, but did not when using Fragmin. Moreover, E456 had no influence on the plasma free fatty acid levels, while Fragmin significantly increased them. Thus, E456 appears to have anticoagulant properties which make it more suitable anticoagulant in extracorporeal circulation than Fragmin.